A new and cryptic species of Trentepohlia (Ulvophyceae, Chlorophyta) from Brazilian mixed forests. Issue 4 (1st July 2018) - Lemes-Da-Silva, Nadia M.; López-Bautista, Juan M.; Branco, Luis Henrique Z.
Abstract: The order Trentepohliales represents one of the most prominent algal groups in terrestrial habitats but its taxonomy and phylogeny are still poorly understood. During a survey of Trentepohliales in different Brazilian biomes, some trentepohlialean populations were found in mixed forest localities growing on the bark of the gymnosperm Araucaria angustifolia . These populations formed orange patches with the typical habit of the genus Trentepohlia . The filaments consisted of cylindrical or swollen cells 4.0–10.2 μm wide and produced single apical globular gametangia and zoosporangia, with apical cells having a well-developed pectic cap. Molecular analysis based on the rbc L gene revealed that these populations represent a distinct clade, and based on the results, a new species, Trentepohlia araucariana, is described.